CHANGES OF WATER QUALITY IN MUDDY BEACHES DUE TO THE INFLUENCE OF EFFLUENT FROM THE COMMUNITY WASTEWATER TREATMENT SYSTEM, THE ROYAL INITIAL ENVIRONMENT RESEARCH AND DEVELOPMENT LAEM PHAK BIA PROJECT - Pholchart, Auttharot; Dampin, Narouchit; Pattamapitoon, Thanit; Wararam, Wacharapong; Chunkao, Kasem (Srinakharinwirot University Journal of Sciences and Technology, 2023)
This research aims to study the change in water quality in muddy beaches affected by effluents from the wastewater treatment system of The Royal Initial Environment Research and Development Laem Phak Bia Project, Phetchaburi Province. Determine the sampling station in the muddy beaches in front of the mangrove forest by surveying 3 lines perpendicular to the coast, consisting of line R as a reference area that does not influence the community wastewater treatment system, lines A and B are received effluent from the community wastewater treatment system., each line has 5 sampling stations. Water samples were collected during the low tide of the highest tide days in October 2019 (rainy season) and February 2020 (dry season). The results showed that the water quality of both seasons was in the Seawater quality standards for aquaculture, when comparing the water quality along with the survey, it was found that TKN, ammonia, and TP in the R line were higher than the A and B line, at 4.7±1.6, 0.019±0.003 and 0.15±0.03 mg/L, respectively, due to household water activities that discharged water into a small canal flowing through the community into the mangrove forest in the R line, unlike the A and B line, which receives effluent from treatment system that is diluted with effluent and is absorbed by mangrove vegetation before it enters the mangrove forest. When comparing seawater quality parallel to that of the coast, there was no significant difference (P < 0.05), and when comparing the water quality in both seasons, it was found that temperature, salinity, EC, TDS, DO, TKN, ammonia, and TP were significantly different (P < 0.05) with salinity, EC, TDS, TKN, ammonia, and TP in the season. The dry season is more valuable than the rainy season, the temperature and DO content in the dry season were lower than in the rainy season due to the effects of seawater and the impact of suspended solids and nutrients from nearby canals, including organic and inorganic substances from the decomposition of living organisms in mangrove forests.